Effect of Education Based on Health Belief Model by Using Virtual Social Network Messenger on Promoting Pediculosis Preventive Behaviors among School Girls - Zahra Joghtaei; Noushin Peyman; Reza Noori; Habibollah Esmaily; Maryam Moradi (Journal of Education and Community Health)
Aims: Pediculosis is one of the most common health problems in children and especially in girls. This study aimed to investigate the effect of education based on the Health Belief Model using social network messenger on promoting pediculosis preventive behaviors among school girls. Materials & Methods: This quasi-experimental study was conducted in Bojnourd in 2018. 145 students were selected through cluster sampling from 12 schools and randomly divided into the intervention and the control groups. For the intervention group, the training program was implemented for 2 weeks and 3 days each week by uploading videos and educational materials about pediculosis in social network messenger. Data collection tools included a questionnaire based on the Health Belief Model and a demographic questionnaire that were completed by the students before, immediately, and 3 months after the education. The data were analyzed by SPSS 20 and by using Chi-square, Exact Fisher, Mann-Whitney, and ANOVA tests. Findings: Based on the results there was a statistically significant relation among the mean scores of awareness, perceived sensitivity, perceived benefits, perceived barriers and self-efficacy in the intervention group, immediately after the intervention compared to before the intervention (p<0.001). Also, mean score of the perceived severity cues to action and behavior increased significantly immediately after the intervention in the intervention group compared to the control group (p<0.05). Conclusion: The results showed that education based on Health Belief Model using the social network messenger is effective in promoting preventive behaviors of pediculosis in girl students.